A fuzzy-ExIWO method for optimal placement of multiple DSTATCOM/DG and tuning the DSTATCM's controller. Issue 3 (3rd May 2016) - Bagheri Tolabi, Hajar; Lashkar Ara, Afshin; Hosseini, Rahil
Abstract : Purpose: – The purpose of this paper is optimal placement of multiple distribution static compensator (DSTATCOM) and Distributed Generation (DG) units along with nonlinear control of the DSTATCOM in order to loss reduction, voltage drop improvement, increase in the voltage stability and improvement of the performance of the controller of the DSTATCOM. Design/methodology/approach: – A combination of a fuzzy system and expanded invasive weed optimization (ExIWO) has been employed for solving the nonlinear/complex problem. A nonlinear control has been designed based on partial feedback linearization (PFL) theory for the DSTATCOM and proportional-integral-derivative (PID) controllers have been employed to trace the reference values. Findings: – A combination of a fuzzy system and ExIWO has been employed for solving the nonlinear/complex problem. A nonlinear control has been designed based on PFL theory for the DSTATCOM and PID controllers have been employed to trace the reference values. Practical implications: – An expandable application was written in MATLAB software to investigate the electrical distribution system with multiple DSTATCOM and DG units by considering the DSTATCOM controller. Originality/value: – First, definition of a new technical and hybrid optimization problem (i.e. optimal placement of multiple DSTATCOM and DG units along with nonlinear controlling of the DSTATCOM). Indeed another important challenge in distribution systems (i.e. optimal placement (size and location) of multiple DSTATCOM and DG units) has been considered along with previous problem (i.e. tuning the DSTATCOM controller). Second, development the objective function and convert it from a purely controlling function to a multi objective function which aims to not only improve the controller of DSTATCOM performance but also aims to reduce the power losses, improve voltage drop and voltage stability. Third, solving the nonlinear-complex problem by a new combination of fuzzy sets and ExIWO algorithm. Fourth, considering two 33 bus and 119 bus distribution test systems and analyzing them in five different scenarios in order to demonstrate the proper performance of the proposed technique for the both small and large systems. Please see the modifications in introduction, problem formulation and simulation results sections.